Genetic control of yellow vein mosaic virus resistance in okra (Abelmoschus esculentus) - YOGESH POPAT KHADE; RAJ KUMAR; RAMESH KUMAR YADAV (The Indian Journal of Agricultural Sciences, 2020)
Yellow vein mosaic virus is the most serious disease of okra which causes severe losses in okra production mainly in the tropics. An experiment was carried out in kharif 2017–18 to understand the inheritance pattern and gene action involved in resistance to yellow vein mosaic virus disease on okra. Based on screening of genotypes, two resistant (DOV-12 and DOV-66) and two susceptible (DOV-1 and Pusa Sawani) parents were identified for this study. The inheritance pattern of okra was studied in six generations (P1, P2, F1, F2, BC1P1 and BC1P2) of four selected crosses (resistant × resistant, two susceptible × resistant and susceptible × susceptible). The Qualitative genetic analysis was done in segregating generations for all the four crosses under study. It revealed that a complementary dominant gene governing the disease resistance in resistant × resistant cross while a single dominant gene was responsible for inheriting resistance in susceptible × resistant cross. The significance of scaling test and joint scaling test also revealed the presence of digenic gene interaction for days to first appearance of YVMV which involved both additive and non-additive gene action. Thus, the present study confirmed the role of genetic architecture of the parents for resistance reaction